The Effect of Stroke Exercise on Blood Pressure in Elderly Patients with Hypertension: A Quasi-Experimental Study - Sri Hartutik; Notasya Devika Arynanda; Sinta Purnama Sari (Indonesian Journal of Global Health Research, 2025)
Hypertension, or high blood pressure, is the leading cause of death worldwide, with essential hypertension accounting for 90-95% of cases. Older people with hypertension are at greater risk of serious complications such as stroke, coronary heart disease, and kidney failure. One form of non-pharmacological intervention that is gaining more attention is anti-stroke exercise. This study aims to determine the effect of stroke sports on blood pressure in the elderly with hypertension. This study used a quasi-experimental design with a pretest and posttest control group design. Two groups were selected: the intervention group, which participated in anti-stroke exercises, and the control group, which did not receive the intervention. The study population was elderly with hypertension who were registered in a health facility or elderly community. The sampling technique used purposive sampling from 30 respondents (15 in the intervention group and 15 in the control group). Data analysis used the Wilcoxon test to determine differences in blood pressure before and after stroke exercises. The Wilcoxon test for the effect of stroke exercises on blood pressure yielded a p-value (0.003 <0.05), indicating differences in blood pressure before and after stroke exercises. The results of the study show that stroke sports are effective in lowering blood pressure in the elderly.